An Approach to the decolonization of peace studies: The intercultural experience and top to bottom of the people Nasa Wes´x Tolima – Colombia - Sandoval Forero, Eduardo Andrés; Capera Figueroa, José Javier (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the article is to discuss in a theoretical and conceptual way the traditional paradigm of modern / colonial research from a decolonizing peace perspective based on the intercultural experience of the people. Nasa Wes´x Tolima - Colombia, regarding the conflict between legal and illegal participants immersed in their territories. The originalityconsists in addressing the problem from the epistemic rupture of interculturality for peace. The method applied was the text analysis research based on indigenous discourses, concluding that the experience of peace of people Nasa Wes’ x joint with the decolonizing and intercultural perspective of peace, when judging the traditional schemes of pacification promoted from the hegemonic State’s interests and dynamics, on the contrary, it appeals to the autonomy and liberation of the mother earth being the reflection of the thought-feeling from the territories in the framework of the peace construction as the motivation of their own struggles for another possible reality in the community sphere.